Rice-Magnaporthe transcriptomics reveals host defense activation induced by red seaweed-biostimulant in rice plants - Banakar, Sahana N.; Prasannakumar, M. K.; Parivallal, P. Buela; Pramesh, D.; Mahesh, H. B.; Sarangi, Aditya N.; Puneeth, M. E.; Patil, Swathi S. (Frontiers in Genetics, 2023)
Red seaweed extracts have been shown to trigger the biotic stress tolerance in several crops. However, reports on transcriptional modifications in plants treated with seaweed biostimulant are limited. To understand the specific response of rice to blast disease in seaweed-biostimulant-primed and non-primed plants, transcriptomics of a susceptible rice cultivar IR-64 was carried out at zero and 48 hours post inoculation with Magnaporthe oryzae (strain MG-01). A total of 3498 differentially expressed genes (DEGs) were identified; 1116 DEGs were explicitly regulated in pathogen-inoculated treatments. Functional analysis showed that most DEGs were involved in metabolism, transport, signaling, and defense. In a glass house, artificial inoculation of MG-01 on seaweed-primed plants resulted in the restricted spread of the pathogen leading to the confined blast disease lesions, primarily attributed to reactive oxygen species (ROS) accumulation. The DEGs in the primed plants were defense-related transcription factors, kinases, pathogenesis-related genes, peroxidases, and growth-related genes. The beta-D-xylosidase, a putative gene that helps in secondary cell wall reinforcement, was down-regulated in non-primed plants, whereas it up-regulated in the primed plants indicating its role in the host defense. Additionally, Phenylalanine ammonia-lyase, pathogenesis-related Bet-v-I family protein, chalcone synthase, chitinases, WRKY, AP2/ERF, and MYB families were up-regulated in seaweed and challenge inoculated rice plants. Thus, our study shows that priming rice plants with seaweed bio-stimulants resulted in the induction of the defense in rice against blast disease. This phenomenon is contributed to early protection through ROS, protein kinase, accumulation of secondary metabolites, and cell wall strengthening.